2011
DOI: 10.1007/s11274-011-0798-z
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cellulase and hemicellulase activities of Thermoascus aurantiacus by xylan hydrolyzed products

Abstract: Thermoascus aurantiacus is able to secrete most of the hemicellulolytic and cellulolytic enzymes. To establish the xylanase inducers of T. aurantiacus, the mycelia were first grown on glucose up until the end of the exponential growth phase, followed by washing and re-suspension in a basal medium without a carbon source. Pre-weighed amounts of xylose (final concentration of 3.5 mg/ml), xylobiose (7 mg/ml) and hydrolyzed xylan from sugarcane bagasse (HXSB) which contained xylose, xylobiose and xylotriose (6.8 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
12
0
2
Order By: Relevance
“…Thus, the T. aurantiacus strain recently isolated from the region of Dourados-MS has considerable potential for the production of xylanase in low-cost culture media (agro-industrial residues). Previous studies have confirmed the potential to produce xylanase by different strains of the same species isolated from other regions (KALOGERIS et al, 1998;DA-SILVA et al, 2005;BRIENZO et al, 2012).…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…Thus, the T. aurantiacus strain recently isolated from the region of Dourados-MS has considerable potential for the production of xylanase in low-cost culture media (agro-industrial residues). Previous studies have confirmed the potential to produce xylanase by different strains of the same species isolated from other regions (KALOGERIS et al, 1998;DA-SILVA et al, 2005;BRIENZO et al, 2012).…”
Section: Resultsmentioning
confidence: 68%
“…However, the highest enzyme production was obtained using wheat bran as substrate, producing 1301.1 U g -1 of dry substrate (or 130.11 U mL -1 ). The production of microbial enzymes by solid-state fermentation is directly related to the nutritional composition and accessibility of the substrate (BRIENZO et al, 2012;STROPARO et al, 2012). Wheat bran is a substrate with good water absorption capacity, and its composition favors microbial cultivation for enzymes production (OLIVEIRA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations